Learning Tortor Martonun Traditional Dance in Simalungun Community - Ruth Hertami; Dilinar Adlin; Ilham Rifandi; Ryan Dallion (Britain International for Academic Research (BIAR) Publisher, 2022)
Batak Simalungun is a part of the five Batak tribes, namely Batak Toba, Batak Karo, Batak Pakpak, and Batak Mandailing, as well as from eight indigenous tribes namely Melayu, Nias, and Sibolga Pesisir in North Sumatra Region. This study aims to explain how the traditional Batak Simalungun dance movement technique in Tortor Martonun, or in Indonesian can be interpreted as a weaving dance. The method used in this research is descriptive-qualitative. The approach used is an ethnographic study with an emphasis on the cultural aspects of the Batak Simalungun tribe. The research location was conducted in Simalungun Regency. The results showed that the Tortor Martonun belonging to the Simalungun community had 20 types of movements consisting of: Mamuyuk (collecting cotton fruit), Manrobus (boiling cotton fruit), Mamispis (separating seeds from cotton), Mamusur (developing), Manusun Bonang (composing thread), Marsigira (coloring), Manjomur Bonang (drying the thread), Mangganti (shaping the thread), Mamuyuk Bonang (taking the thread), Partorsahon Bonang (tidying the thread), Manggulung Bonang (rolling the thread), Martonun (weaving), Manggulung bonang (winding thread), Papeakkon Bonang (putting/placing the thread), Martonun (weaving), Mambuka Hiou (untying the woven/traditional woven cloth), Patorsahon Hiou (tidying the hiou), Pataridahkon Hiou (showing hiou), and Panutup (closing). To facilitate the learning process of Tortor Martonun while responding to technological advances, the entire range of motion is packaged in its entirety in audio-visual media, and uploaded to podcast “Rumah Tari’. with a link link Youtube : https://www.youtube.com/channel/UCYn7jZKYq0mEVgjWajsInag